PRECERAMIC PERIOD IN THE VALLEY OF YARABAMBA, AREQUIPA - Umire Alvarez, Adán (2015)
The era of hunter - gatherers (ca. 10.000 to 2.000 BC), is an issue that has not been completed in the immediate vicinity to the Arequipa city. Research on this important period are explained using sites such as larger and more complex Sumbay caves in the high plateau, or the shell middens from Camana, in the coast, or Puyenca near to Mollendo on the coast, important archaeological sites but distantly located with respect to the Arequipa valley. In this article the presence of pre-ceramic archaeological sites in streams that flow into the river Yarabamba evaluated. Similarly the location of a small shelter with rock art in the gorge of Cachiwasi (seasonally dry river Yarabamba tax) reporting. Recent data suggest that the system composed of river-Quequeña-Yarabamba Sogay and confluent streams have the potential not intended for the elucidation of some problems related to the period of hunter-gatherers in the puna dissimilar environments.